Similarities between 2D and 3D convection for large Prandtl number - PANDEY, AMBRISH; VERMA, MAHENDRA K; CHATTERJEE, ANANDO G; DUTTA, BIPLAB (Pramāṇa, 2016)
Using direct numerical simulations of Rayleigh–Bénard convection (RBC), we perform a comparative study of the spectra and fluxes of energy and entropy, and the scaling of large-scale quantities for large and infinite Prandtl numbers in two (2D) and three (3D) dimensions. We observe close similarities between the 2D and 3D RBC, in particular, the kinetic energy spectrum E u ( k )∼ k −13/3 , and the entropy spectrum exhibits a dual branch with a dominant k −2 spectrum. We showed that the dominant Fourier modes in 2D and 3D flows are very close. Consequently, the 3D RBC is quasi-two-dimensional, which is the reason for the similarities between the 2D and 3D RBC for large and infinite Prandtl numbers.